Impact of Reduced Anthropogenic Emissions Associated With COVID‐19 Lockdown on PM2.5 Concentration and Canopy Urban Heat Island in Canada - Samaneh Ashraf; Francesco S. R. Pausata; Sylvie Leroyer; Robin Stevens; Rodrigo Munoz‐Alpizar (GeoHealth)
Abstract Extensive lockdowns during the COVID‐19 pandemic caused a remarkable decline in human activities that have influenced urban climate, especially air quality and urban heat islands. However, the impact of such changes on local climate based on long term ground‐level observations has hitherto not been investigated. Using air pollution measurements for the four major Canadian metropolitan areas (Toronto, Montreal, Vancouver, and Calgary), we find that PM2.5 markedly decreased during and after lockdowns with peak reduction ranging between 42% and 53% relative to the 2000–2019 reference period. Moreover, we show a substantial decline in canopy urban heat island intensity during lockdown and in the post lockdowns periods with peak reduction ranging between 0.7°C and 1.6°C in comparison with the 20‐year preceding period. The results of this study may provide insights for local policymakers to define the regulation strategies to facilitate air quality improvement in urban areas.